SISTEM INFORMASI KEPENDUDUKAN DAN CATATAN SIPIL MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING (STUDI KASUS PEMERINTAH DAERAH) - Iyan Gustiana (Jurnal Manajemen Informatika (JAMIKA), 2013)
In conducting its role as the local government administrator, Pemda has authoritative duties; they are, among others, organizing citizenship service products and citizenship registration office. Citizenship service products are services given to the citizens that include providing issues of Family Cards (KK) and Identity Card (KTP). Citizenship registration office, on the other hand, provides services of issuing birth certificates.Pemda, therefore, requires an architecture planning to be designed along the line with the products of citizenship services. The architecture design applied here is the Enterprise Architecture Planning (EAP) conveying the framework model by Zachman. In developing this architecture.The result of this research is offered to Pemda as a proposition in the form of recommendation & documentation of planning of architecture data, architecture application, and architecture technology. This design is hoped to become a reference in providing better supports in citizenship services for the society in the future.